Pier+Ocean : Construction in the art of the seventies - von Graevenitz, Gerhard; Dilworth, Norman; Barker, Barry; Hayward Gallery, London; Rijksmuseum Kröller-Müller, Otterlo (London : Arts Council of Great Britain, 1980)
Baljeu, Joost ; Baumgarten, Bodo ; Buren, Daniel ; Colombo, Gianni ; De Maria, Walter ; Gorin, Jean ; Huebler, Douglas ; Insley, Will ; Knoebel, Wolf ; Sandback, Fred ; Shapiro, Joel ; Simonds, Charles ; Smithson, Robert ; Tuttle, Richard ; Wasko, Ryszard ; Weiner, Lawrence ; etc.
Pier+Ocean : Construction in the art of the seventies : An exhibition selected by Gerhard von Graevenitz assisted by Norman Dilworth, Hayward Gallery, London, 8 May to 22 June 1980 ; Rijksmuseum Kröller-Müller, Otterlo, 13 July to 8 September 1980
boek